2022
DOI: 10.1155/2022/2751750
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced-Dose Statins for ST-Segment Elevation Myocardial Infarction Patients after Emergency Percutaneous Coronary Intervention

Abstract: Background. Acute ST-segment elevation myocardial infarction (STEMI) is a serious multiple acute cardiovascular disease. This study investigated the effect of statins on the efficacy and prognosis of STEMI patients after emergency PCI. Methods. From October 2019 to January 2021, 98 patients with STEMI in our hospital were selected and divided into study group and control group. The study group took atorvastatin 40 mg 2 hours before surgery, 40 mg/day after surgery, and 20 mg/day 1 week later. The control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Currently, a number of clinical trials reported that atorvastatin, simvastatin and rosuvastatin administered prior to PCI reduced the incidence of MACE (28)(29)(30)(31). Among these drugs, rosuvastatin is able to regulate blood lipid levels by inhibiting cholesterol synthesis and consequently suppressing the formation of atherosclerosis; furthermore, its half-life period is relatively longer and its lipid-lowering effect is relatively better compared with other statins (32).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a number of clinical trials reported that atorvastatin, simvastatin and rosuvastatin administered prior to PCI reduced the incidence of MACE (28)(29)(30)(31). Among these drugs, rosuvastatin is able to regulate blood lipid levels by inhibiting cholesterol synthesis and consequently suppressing the formation of atherosclerosis; furthermore, its half-life period is relatively longer and its lipid-lowering effect is relatively better compared with other statins (32).…”
Section: Discussionmentioning
confidence: 99%
“…ST-segment elevation myocardial infarction is a moderate, acute and serious disease of cardiovascular disease ( 36 ). In the face of STEMI patients, the most effective treatment measure is reperfusion treatment ( 37 ).…”
Section: Discussionmentioning
confidence: 99%